Analisis Penerapan Sistem Informasi Akuntansi Klaim Jaminan Kematian Studi Kasus AJB Bumiputera 1912 Kantor Wilayah Medan - Yolanda Tawabina; Yenni Samri Julianti Nasution; Nurwani Nurwani (Universitas Labuhanbatu, 2023)
This study aims to determine and analyze the application of Accounting Information System of death insurance claims at AJB Bumiputera 1912 Medan Regional Office. This type of research is qualitative research. The subjects of this study were insurance customers and staff employees. The data of this study were collected through interviews and document studies. The primary Data came from customer interviews and related staff employees, while the secondary data came from books, journals and documents. The method of analysis used is descriptive qualitative. The results of this study indicate the implementation of the Accounting Information System of death insurance claims at AJB Bumiputera 1912 Medan Regional Office has been using a computerized system in accordance with existing regulations. It is based on the elements that are the basis for the implementation of an adequate accounting information system in the form of forms and records. The effectiveness of the death insurance claim system at AJB Bumiputera 1912 Medan Regional Office as a whole has not been effective. The number of obstacles to the Accounting Information System filing a death insurance claim at AJB Bumiputera 1912 Medan Regional Office can be seen by the number of insurance participants who filed claims did not complete the documents in accordance with the requirements that have been determined so as to slow down the process of disbursement of claims. Barriers to computer systems that sometimes experience buffering and the use of digital systems to support the activities of the company and customers have not been realized.